Impact of centralization of care for malignant peritoneal mesothelioma: A historical cohort study from the Dutch mesothelioma expert centers. Issue 3 (March 2023) - van Kooten, Job P.; de Gooijer, Cornedine J.; von der Thüsen, Jan H.; Brandt-Kerkhof, Alexandra R.M.; Albers, Arend G.J.; Lahaye, Max J.; Monkhorst, Kim; Burgers, Jacobus A.; Aerts, Joachim G.J.V.; Verhoef, Cornelis; Madsen, Eva V.E.
Abstract: Background: Malignant peritoneal mesothelioma (MPM) is a rare and aggressive cancer that has a poor prognosis. An earlier population-based study found that the majority of Dutch patients do not receive anti-cancer treatment. In 2015, Dutch Malignant Mesothelioma care was centralized in two expert centers. We reviewed treatment patterns at these centers, to assess the impact of centralization of MPM care in the Netherlands. Methods: Data from all patients referred to the Dutch MPM expert centers from 2014 to 2020, were retrospectively collected. Descriptive statistics regarding referrals, patient and tumor characteristics, and treatment patterns were provided. Population-based incidence rates were provided by the Netherlands Cancer Registry. Results: From 2014 to 2020, 78 patients were referred to the Dutch Mesothelioma expert centers, of whom 32 were female (41%). From 2014 to 2017, 27 patients were referred, whereas 51 patients were referred from 2018 to 2020. This represents about 24% and 61% of the estimated population incidence, respectively. Treatment patterns were comparable between both periods. Between 2014 and 2018, 33% of patients underwent surgery, 44% systemic therapy, and 22% received best supportive care (BSC), while this was 29%, 37%, and 33% respectively from 2018 to 2020. Conclusion: Centralization of care for patients with MPM resulted in an increase of annual referrals to the Dutch mesothelioma expert centers. While population-based incidence did not change during the study period, the absolute number of patients receiving treatment at our centers did increase. This might be considered a first important step towards better treatment for patients with this fatal disease.